2006
DOI: 10.1073/pnas.0510115103
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of gene expression in pathophysiological states: Balancing false discovery and false negative rates

Abstract: Nucleotide-microarray technology, which allows the simultaneous measurement of the expression of tens of thousands of genes, has become an important tool in the study of disease. In disorders such as malignancy, gene expression often undergoes broad changes of sizable magnitude, whereas in many common multifactorial diseases, such as diabetes, obesity, and atherosclerosis, the changes in gene expression are modest. In the latter circumstance, it is therefore challenging to distinguish the truly changing from n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 23 publications
0
47
0
Order By: Relevance
“…The false discovery rate has been well described to be a suitable method for microarray analysis and has become one of the most important standards by which genes showing significant changes in transcription are listed and sorted (40,42,51). In a recent proteomic study, researchers compared t statistics and SAM methods to analyze the liquid chromatography-mass spectrometry (LC/MS) proteomic data, and the results indicated that SAM identified a large number of different expressed proteins while overcoming the false-positive results that one would encounter with a t test (50).…”
Section: Resultsmentioning
confidence: 99%
“…The false discovery rate has been well described to be a suitable method for microarray analysis and has become one of the most important standards by which genes showing significant changes in transcription are listed and sorted (40,42,51). In a recent proteomic study, researchers compared t statistics and SAM methods to analyze the liquid chromatography-mass spectrometry (LC/MS) proteomic data, and the results indicated that SAM identified a large number of different expressed proteins while overcoming the false-positive results that one would encounter with a t test (50).…”
Section: Resultsmentioning
confidence: 99%
“…Procedures can be applied to correct for multiple testing, such as the family-wise error rate (FWER) or the false discovery rate (FDR) (20,46). However, these procedures can be overly stringent, resulting in identification of only the most important changes and possibly discarding other relevant genes (31).…”
Section: Gene Selectionmentioning
confidence: 99%
“…This is especially true in nutrition, where dietary interventions result in modest, but biologically important gene expression changes (1,12,33). In the medical field it is also increasingly recognized that the more subtle changes contribute importantly to the outcome (30,31,38).…”
mentioning
confidence: 99%
“…Storey (2007) proposes an optimal discovery procedure based on maximizing Expected True Positives (ETP) for each Expected False Positive (EFP) among all Single Thresholding Procedures (STP). Norris and Kahn (2006) have proposed balanced probability analysis (BPA) based on three variables: (i) The total number of true positives (TTP); (ii) The false discovery rate (FDR), defined as the aggregate chance that a true null hypothesis is rejected by statistical accident. (iii) The false negative rate (FNR), defined as the number of hypothesis that should truly be rejected but are missing from the significance list divided by the total number of hypothesis that should truly be rejected.…”
Section: Introductionmentioning
confidence: 99%
“…As Norris and Kahn (2006) have argued, the true FDR can be accurately determined only when the TTP is known. They used an adaptation of the algorithm by Storey and Tibshirani (2003) they estimate the TTPs.…”
Section: Introductionmentioning
confidence: 99%